Analysis of Obstacles For Mangosteen Agro-Industry Revitalization In Karacak Agropolitan Area, Indonesia: An Interpretive Structural Modeling Approach - Oryzanti, Parwa; Wardah, Wardah; Setiawan, Marwan; Purnamasari, Riska Ayu; Kusumawaty, Rini; Purwaningsih, Ratna; Rustiadi, Ernan (National Research and Innovation Agency, Indonesia, 2024)
This study aims to identify and propose solutions to the obstacles faced in the study of Karacak Agropolitan Revitalization based on Mangosteen agroindustry in Bogor Regency as outlined in a structural model. The revitalization of agro-industry-based agropolitan areas is studied through science, technology, and innovation which are then formulated and analyzed with the Interpretive Structural Modeling Method. Primary data were collected through expert-based surveys and questionnaires from seven relevant and representative government agencies to formulate policy studies. This research resulted in a study of 9 sub-elements of constraints and found 1 key sub-element, arrange hierarchically based on its importance. At the most critical level, we identified the government's political will towards agro-industrial development incentives and disincentive programs in agropolitan areas. This study recommends the government start an integrated agropolitan area revitalization program by utilizing local biological resources. The systems model approach will facilitate sustainable development at the village level, promoting inclusive economic growth and resilience. Keywords: Agropolitan, Barriers, Interpretive Structure Modeling, Mangosteen Agroindustry.